Breastfeeding, weaning, and dietary practices during the Western Zhou Dynasty (1122–771 BC) at Boyangcheng, Anhui Province, China. Issue 2 (13th November 2017) - Xia, Yang; Zhang, Jinglei; Yu, Fei; Zhang, Hui; Wang, Tingting; Hu, Yaowu; Fuller, Benjamin T.
Abstract: Objectives: Here we investigate breastfeeding and weaning practices and adult dietary habits at the Western Zhou Dynasty (1122–771 BC) site of Boyangcheng (薄阳城) located in Anhui Province, China. In addition, we utilize the differences in bone collagen turnover rates between rib and long bones from the same individual to examine past life histories, such as changes in diet or residence. Materials and methods: Bone collagen from both the rib and long bones (either femora or humeri) of 42 individuals was measured for stable isotope ratios of carbon (δ 13 C) and nitrogen (δ 15 N). In addition, δ 13 C and δ 15 N values are reported for 35 animals (dogs, cows, horses, pigs, and deer). Results: The human δ 13 C values range from −20.7‰ to −12.0‰ with a mean value of −18.8 ± 1.6‰. The human δ 15 N values range from 9.1‰ to 13.4‰ with a mean value of 10.9 ± 1.0‰. The animals display a wide range of δ 13 C (−21.5‰ to −8.2‰; −15.8 ± 4.5‰) and δ 15 N values (4.0‰ to 9.5‰; 6.5 ± 1.8‰). Conclusions: The adult δ 13 C and δ 15 N results indicate that mixed C3 (rice) and C4 (millet) terrestrial diets with varying levels of animal protein (mostly pigs and deer) were consumed. The elevated subadult δ 15 N results return to adult levels by approximately 3–4 years of age, indicating that the weaning process was completed during this period. Individuals between 2 and 10 years old, with lower δ 13 C and δ 15 N results than the adult mean, possibly consumed more plant‐based diets, and this is consistent with Chinese medical teachings ∼1500 years later during the Tang Dynasty (AD 618–907). The isotopic offsets between the ribs and long bones revealed that five adults experienced dramatic dietary shifts in their later lives, switching from predominately C3 /C4 to C3 diets. This research provides the first isotopic information about ancient Chinese breastfeeding and weaning practices and establishes a foundation for future studies to examine diachronic trends.